MEDIA INFORMATION ON RELIGIOUS HARMONY: DIGITAL COMMUNICATION OF FKUB MEDAN CITY IN THE DEVELOPMENT AGENDA BASED ON SDGS 16 - Khairiah, Nona; Sazali, Hasan (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study aims to analyze the digital communication strategy implemented by the Medan City Interfaith Harmony Forum (FKUB) in framing the narrative of interfaith harmony in the digital public space, as well as its contribution to achieving Sustainable Development Goal (SDGs) number 16. The approach used is qualitative with a case study type. Data were collected through non-participatory observation of FKUB social media content, visual and narrative documentation, and a study of institutional documents. Data analysis follows the Miles, Huberman, and Saldaña model, including the process of collecting, condensing, presenting, and verifying data through source triangulation. The results of the study show that FKUB Medan City not only plays a role as a social-religious mediation institution, but also as an active public communication actor in voicing the values of tolerance through information media. The content produced includes peace declarations, symbolic interfaith campaigns, and participation in youth activities. This strategy has proven relevant in supporting SDGs 16 indicators such as strengthening inclusive institutions, reducing violence, and expanding access to public information. The novelty in this study lies in the integration of the Project Cycle Management (PCM) approach to systematically map FKUB mediation strategies, which have not been widely touched upon in previous studies. This study recommends strengthening FKUB institutional capacity through digital training, integration of SDGs-based policies, and replication of social media-based harmony communication models in other regions.